2010
DOI: 10.5539/ijbm.v5n6p46
|View full text |Cite
|
Sign up to set email alerts
|

Students’ attitude towards the Uses of Internet

Abstract: Internet is a useful tool for all in a technologically advanced world. Internet use for education is very important. It is now in practice to teach school to college to get more out of it. In this study, the emphasis is given on the most important success factor that investigates about Internet usage by students of the University, whether it is an effective learning tool for students and teachers and also examines the level of use Internet and whether the Internet is useful for distance learners. The sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
2
8
0
1
Order By: Relevance
“…These findings are in line with other studies in Saudi Arabia (Al Otaibi, 2012) and in other contexts (Abedalaziz et al, 2013;Al Mahmud, 2011;Hong et al, 2003;Israel, 2013;Luan et al, 2005;Peng et al, 2006;Rehman et al, 2010). Interestingly, the statistical findings of the present study have indicated that demographic variables including age, program of study, and year of study had no effect on student attitudes towards the Internet.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These findings are in line with other studies in Saudi Arabia (Al Otaibi, 2012) and in other contexts (Abedalaziz et al, 2013;Al Mahmud, 2011;Hong et al, 2003;Israel, 2013;Luan et al, 2005;Peng et al, 2006;Rehman et al, 2010). Interestingly, the statistical findings of the present study have indicated that demographic variables including age, program of study, and year of study had no effect on student attitudes towards the Internet.…”
Section: Discussionsupporting
confidence: 83%
“…Students respond positively to the Internet as a functional technology (Peng et al, 2006), a learning tool (Al Mahmud, 2011;Hong et al, 2003), and a provider of substantial information (Rehman et al, 2010).…”
Section: Experience With and Attitudes Towards The Internetmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have found that pre-service teachers have positive IA towards using the Internet (Luan, Fung, & Atan, 2008;Rehman, Hunjra, Safwan, & Ahmad, 2010;Wong, Kamariah, Ramlah, Rohani, & Tang, 2003). However, Rehman et al (2010) state that the participants in their study mentioned the difficulties of Internet usage in school. Luan et al (2008) found that pre-service teachers' Internet usefulness perceptions were rather low.…”
Section: Internet Attitude (Ia)mentioning
confidence: 99%
“…According to Oxford dictionary "Internet is an international computer network connecting other networks and computers from companies, universities, NGOs etc." The internet is a useful tool for all in a technologically sophisticated world (Rehman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%